NATIONAL DEFENSE POLICY AND THE PROTECTION OF THE CRITICAL ENERGY INFRASTRUCTURE IN BRAZIL - Paiva, Iure (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The study developed in this paper aims to analyze how the protection of Brazil’s critical energy infrastructure is dealt with under the national defense policy in order to better understand how the military dimension of energy security is outlined in Brazil. With the intention of achieving this goal, it seeks, initially, to identify which are and where are located the main Brazilian critical energy infrastructure relating to the oil chain, petroleum products and natural gas. Next, it aims to examine the extent to which the protection of such structural complexes is provided for in the national defense policy, particularly in the main documents dealing with the subject in the country. Finally, it observes how is the planning of the Brazilian offensive and defensive military power in the prevention and response to threats against the infrastructure related to the above-mentioned sources.